Analisis Penerapan PSAK No. 24 Tentang Imbalan Kerja: Studi Kasus pada PT. XYZ - Zumrotil Auliya; Rini Febrianti; Putri Nailah Azahra; Dhio Gon zales; Siti Rodiah (Publikasi Inspirasi Indonesia, 2025)
This study aims to analyze the implementation of Financial Accounting Standards Statement (PSAK) No. 24 concerning Employee Benefits at PT. XYZ, a construction service company currently in the development stage. The study uses a qualitative descriptive approach with data collected through interviews with the company’s management and permanent employees. The results show that PT. XYZ has implemented short-term employee benefits such as salaries, fixed allowances, bonuses, overtime pay, paid leave, and social security in accordance with PSAK 24 regulations. However, the company has not yet implemented post-employment benefits, other long-term employee benefits, or termination benefits. This is due to the company's early stage and focus on operational and financial stabilization. The study recommends developing long-term employee benefits policies and more comprehensive employment documentation to ensure PT. XYZ's financial reporting complies with applicable accounting standards.